Mecanismos celulares de la adicción a la cocaína: base para un tratamiento medicamentoso - Trelles, Luis (1988)
The clinical signs and symptoms of cocaine adiction and withdrawal are exposed and its neurophysiological basis explained.  A combination of drug therapy, desensibilation and psychotherapy is proposed as the best treatment for this addiction.